Efeito do extrato de Vatairea macrocarpa (Benth) Ducke na modulação do perfil de expressão de mRNAs em fígado de ratos diabéticos - Almeida, Fhelipe Jolner Souza de (2016)
Diabetes mellitus is a metabolic disorder which the development and progression is directly associated with changes in expression of genes involved in the insulin production and response. The Vatairea macrocarpa (Benth.) Ducke has ethnopharmacological indication for the diabetes treatment and was already proved its antidiabetic potential. In this context, goal was to investigate the effects of crude extract of V. macrocarpa in the mRNAs expression, pratice in liver of diabetic rat in order to provide evidence of the pharmacologic action of this plant. RNA profile from the liver of diabetic rats treated and non treated with V. macrocarpa extract were investigated. The extract affects the transcription of 639 genes from which 51 are differentially expressed. Among the differentially expressed genes were identified genes encoding regulatory enzymes of glycolysis (pyruvate kinase) and gluconeogenesis (phosphoenolpyruvate carboxykinase) and fundamental for glucose homeostasis. Genes involved in the oxidation of lipids (acyl-CoA synthetase and Carnitine O-acetyltransferase) and lipogenesis (acetyl-CoA carboxylase, malic and stearoyl-Coenzyme A desaturase 1 enzymes) and amino acid metabolism (serine dehydratase and enzyme aminocarboxymuconato semialdehyde decarboxylase) , which participate in energy metabolism control were also modulated by treatment with the extract. These data indicate that administration of the extract to diabetic rats modulates genes with cellular functions essential for the control of altered metabolic pathways in diabetes and opens new perspectives in relation to their pharmacological potential, since it promoted the change in other 166 genes with molecular and celular functions that were not contemplated in this work.